(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the context of continuous education, we have identified the main principles of the diversification process as continuous change, individual orientation, alternative options, humanism, and innovation. In this article, we will explore the characteristics of each principle and examine their collective impact on the quality of education.